PERAN MANAJEMEN ASET DALAM PEMBANGUNAN DAERAH - Aras Aira (Kutubkhanah, 2015)
Regional assets is an important resource for local government, which contribute to increase revenue and have a role in regional development. Regional development in the era of regional autonomy has the goal: improving welfare of local people and all citizens of indonesia. Asset management is one way to achieve regional developmnet objectives, asset management has the following roles: provide transparency and accountability in the management, supervision and control. Identifying regional economic, optimizing local revenue, fixing work organizations, systems and procedures to improve public services, respond to changes and growth in the perspective of regional autonomy regional and global, improving and creating a new image, increase investment and boost economic growth area